A Correlation between Mothers' Knowledge and Exclusive Breastfeeding in the Working Area of Sawah Lebar Health Center in 2025 - Indah Selviana; Liya Lugita Sari; Yesi Putri (Utami Publisher, 2026)
The World Health Organization (WHO) has issued child growth standards that are applied throughout the world. These standards emphasize the importance of exclusive breastfeeding for infants from birth to 6 months of age, which means that infants receive only breast milk from their mothers or from caregivers requested by their mothers to provide breast milk, without the addition of other liquids or solid foods, except for syrups containing vitamins, supplements, minerals, or medicines. The purpose of this study is to determine a correlation between mothers' knowledge and exclusive breastfeeding in the working area of Sawah Lebar Health Center in 2025. This study used a cross-sectional research method. The population in this study was all breastfeeding mothers. The sample in this study consisted of 35 respondents using purposive sampling. The research instrument used a questionnaire. Data analysis was performed using univariate and bivariate methods. The results showed that 31.4% of respondents had insufficient knowledge, and 48.6% did not practice exclusive breastfeeding. It is hoped that health services will provide information to increase exclusive breastfeeding